Predictors of satisfaction with life among second generation migrants - Félix Neto (1995)
As a part of a comprehensive study of the psychological acculturation of Portuguese youth born in France, this paper examines the relationship between satisfaction with life and some psychosocial variables. The sample consisted of 519 Portuguese youth resident in Paris (47% were male and 53% female). The following instruments were administered to all subjects: the Satisfaction With Life Scale, the acculturative Attitudes Scales, the Social Anxiety Scale, two brief measures of (a) loneliness and (b) locus of control as well as a background inventory. As expected no gender differences were found, but there were significant effects on satisfaction with life related to religion, participation in an association, number of Portuguese friends and ethnic identity. Expressed satisfaction with life showed significant negative correlations with perceived difficulties of adaptation, marginalization, social anxiety, and loneliness; and positive correlations with integration and locus of control. Multiple regression analysis used to determine the significant predictor variables of satisfaction with life indicated that the strongest predictors were loneliness and perceived state of health.